The Comparison of Bundle-Pricing Scheme Models Using Quasi-Linear Utility Function - Fitri Maya Puspita; Evi Yuliza; Muthia Ulfa (INSIST, 2016)
Abstract—— In this paper, we formulate bundle-pricing modified models involving pricing scheme based on quasi-linear utility function as one of internet service provider (ISP) main goal is to maximize their profit. The model formed by setting cost of creating bundle and total reservation price of customer i’s. LINGO 11.0 is used to solve the models to obtain the optimal solution. The solver result for each case either from original model and modified model are compared to obtain the optimal solution. The result showed that for each case based on 3-pricing schemes which are flat fee, usage based and two-part tariff, ISPs gain the same profit with the original model but ISPs save more time in terms of resources rather than the original model. ISP’s may use this model as consideration for setting cost of creating a bundle and total reservation price of customer in maximizing profits and also to provide better service quality for customers with their preferences exactly.Keywords— bundle pricing, utility function, pricing strategies, optimal solution.